Prevenção Quaternária: envelhecendo em sociedades medicalizadas - Borrozzino, Nélio Fernandes (2019)
Why is it prescribed so much for the elderly? It was based on this questioning that unfolds from my clinical practice as a nurse, in which I was confronted with its negative consequences – the drug iatrogenies – that I was motivated to carry out this research. Thus, my general objective was defined: to bring to light the problematic that involves, in the present societies, the growing use of drugs by the elderly, and in particular, to discuss the determinants of their iatrogenic effects. I proceeded from the hypothesis that there was some relation between this fact and that of living in medicalized societies, marked by the exacerbation of a prescriptive culture. In this perspective, my specific objectives were: (1) to rescue the way of constitution of the dynamics that responded, in the contemporaneity, by the medicalization of human life; (2) to identify the way in which pertinent literature has discussed the inappropriate use of drugs by the elderly, specifically addressing their iatrogenic effects; (3) to carry out field research with medical professionals to listen to them about the problem issue that this dissertation raises, opening space for a better understanding of the articulation between theory and clinical practice with the elderly. From a methodological point of view, this dissertation has a bibliographic review of the theme (chapter 1 and 2) that is pertinent to it and its articulation with the analysis / interpretation of data collected in a field research (chapter 3). The qualitative methodological approach, with an exploratory character, counted on the accomplishment of a semi-structured interview, carried out with seven physicians of different profiles that work with elderly patients. The results of the analysis indicate that there is a gap in training, not only in the teaching of Pharmacology, but also in the subjects of Geriatrics and Gerontology. Another relevant point concerns the recognition that drug iatrogeny may have as one of its determinants the removal, in modern medicine, of the doctor of the sick person's word. To this extent, the research indicated that it is necessary to recognize the importance of listening, as well as auscultation, in the prevention of drug iatrogenies in the elderly (what is called quaternary prevention). Finally, I was able to understand how in the medicalized culture, each one of us, laymen or health professionals, can become inducers of iatrogeny. If this does not happen, a cultural change is necessary. At its foundation is the recognition that human life is the fruit of a miscegenation between the biological, the psychological and the social. From this perspective, the possibility opens up for a more integral / integrative vision to be presented as a basis for avoiding excessive prescriptions at any stage of life and, especially, in old age